Building resilience through human centered interventions: A case study of female smallholder farmers in Matuu, Kenya - Mutiso, Ashley; Vait, Samuel; Magati, Okari (Itanya Africa Group, 2023)
This paper explores the findings of a baseline study conducted in Matuu Ward, Machakos County, Kenya, focusing on the needs, challenges, and aspirations of female smallholder farmers. The study employed focus group discussions and a desk review of existing information to collect data. The findings reveal that female smallholder farmers in the region face obstacles such as limited access to finance, knowledge, technology and markets. These challenges result in lower agricultural yields, increased vulnerability to climate change and heightened poverty levels. The social context of the farmers highlights the predominant role of men in decision-making, leaving out women in the making of life-changing decisions. The study also identifies various challenges they face, including lease agreement issues, market linkages, environmental concerns such as deforestation and soil degradation, and health-related problems such as water pollution, limited access to healthcare and behavioral biases toward receiving specific interventions, as challenges impacting women’s agricultural productivity. As part of an ongoing project, the study recommends social capital and community resilience interventions, capacity building, improved financial structures, women’s empowerment programs, and climate change adaptation and mitigation measures to increase resilience. This paper argues for a better understanding of the gendered dynamics within the context of women smallholder farmers for designing targeted interventions that address their specific needs. By enhancing their adaptive and transformative capacities, these interventions can contribute to building resilience, reducing gender inequality and promoting sustainable agricultural practices.